Covid-19 in Wales: “One Team Wales” and/versus “Team UK”? - Stéphanie Bory (Revue Française de Civilisation Britannique)
There is no doubt that the Covid-19 pandemic, affecting the UK and the rest of the world since March 2020, put the Welsh Government, especially Mark Drakeford, the First Minister, in the limelight, not just in Wales, but all over the UK. Indeed, health being a devolved matter, some Welsh people came to realise they had a parliament and government able to devise a made-in-Wales policy. If, at the beginning of the pandemic, policies were much the same across England and Wales, the two countries quickly differed in their approach to tackling the crisis and implementing lockdown rules. And yet, the Welsh Government, due to its limited economic – especially budgetary and fiscal – powers, also had to adapt to decisions made by the British Government. It seems that the handling of the pandemic compounded the tensions between Boris Johnson’s and Mark Drakeford’s governments, at a time when the British Prime Minister was trying to recentralise power in London.